2021
DOI: 10.3389/fpsyg.2021.690690
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Awareness of College Student Startup Entrepreneurs Toward Mass Entrepreneurship and Innovation From the Perspective of Educational Psychology

Abstract: Against the background of economic globalization, the awareness of college student startup entrepreneurs toward mass entrepreneurship and innovation is analyzed from the perspective of educational psychology, thus responding to national development strategies. First, the status quo of innovation and entrepreneurship education is understood by literature analysis. Second, the existing innovation and entrepreneurship education in colleges and universities is investigated with a questionnaire survey (QS) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…With respect to research subjects, those who engage in innovative behavior include enterprise employees, 2 scientific researchers, 10 entrepreneurs, 11 teachers, 12 and students. 13 The key to innovation in colleges and universities depends upon students, and their innovative behavior determines the competitiveness of colleges and universities and even the country to a certain extent. 13 The research question is what kind of innovative behavior do students exhibit since the Ministry of Education of China implemented a training program for students’ innovation and entrepreneurship?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to research subjects, those who engage in innovative behavior include enterprise employees, 2 scientific researchers, 10 entrepreneurs, 11 teachers, 12 and students. 13 The key to innovation in colleges and universities depends upon students, and their innovative behavior determines the competitiveness of colleges and universities and even the country to a certain extent. 13 The research question is what kind of innovative behavior do students exhibit since the Ministry of Education of China implemented a training program for students’ innovation and entrepreneurship?…”
Section: Introductionmentioning
confidence: 99%
“… 13 The key to innovation in colleges and universities depends upon students, and their innovative behavior determines the competitiveness of colleges and universities and even the country to a certain extent. 13 The research question is what kind of innovative behavior do students exhibit since the Ministry of Education of China implemented a training program for students’ innovation and entrepreneurship? In management practice, how does one stimulate students’ innovative behavior by improving personal motivation and the innovative climate?…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the status quo of entrepreneurship education in colleges and universities through questionnaires and interviews. Only a very few students have clear seriousness and enthusiasm for entrepreneurship ( Liu and Yu, 2021 ). There are also studies of the effect of entrepreneurship education in universities using online and offline survey methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing number of scholars have begun to focus on the fact that the combination of entrepreneurial psychology and entrepreneurship research can enrich and improve the current theoretical framework of entrepreneurship ( Frese and Gielnik, 2014 ), and some researchers have addressed the relationship between entrepreneurial psychology and entrepreneurial motivation in the transportation industry ( Shi and Wang, 2021 ), while other researchers have added the psychology of entrepreneurship in college students to the study of entrepreneurial cognitive interaction ( Liu and Yu, 2021 ). Therefore, this study first selects the positive elements of entrepreneurial psychology as the first element that shapes the process of establishing a new venture, which includes optimism, passion, and self-efficacy, all of which have been demonstrated empirically by research identifying their exact impact on entrepreneurial behavior and decision-making ( Prandelli et al, 2016 ; Xie et al, 2016 ; Gu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research showed that different dimensions of entrepreneurial self-efficacy played a partial mediated and fully mediated role between the independent personality and entrepreneurial intention of migrant workers ( Chen et al, 1998 ; Wilson et al, 2007 ; Kasouf et al, 2015 ; Tantawy et al, 2021 ). However, most studies on entrepreneurial self-efficacy have focused on college students and corporate entrepreneurship ( Huang et al, 2021 ; Liu and Yu, 2021 ; Zelin et al, 2021 ), and, however, few scholars have studied farmers’ entrepreneurship in the context of rural revitalization in China. The article constructs a mechanistic model of farmers’ entrepreneurial behavior from the perspectives of entrepreneurial attitude and entrepreneurial environment, and uses a structural equation modeling approach to test it empirically in order to provide empirical support for the complex mechanisms among entrepreneurial attitude, entrepreneurial environment, entrepreneurial self-efficacy, and farmers’ entrepreneurial behavior.…”
Section: Introductionmentioning
confidence: 99%